Prospective evaluation of blood Epstein–Barr virus DNA load and antibody profile in HIV-related non-Hodgkin lymphomas. (1st May 2021) - Lupo, Julien; Germi, Raphaële; Lancar, Rémi; Algarte-Genin, Michèle; Hendel-Chavez, Houria; Taoufik, Yassine; Mounier, Nicolas; Partisani, Marialuisa; Bonnet, Fabrice; Meyohas, Marie-Caroline; Marchou, Bruno; Filippova, Anastasiia; et al.
Abstract : Objectives: The value of Epstein– Barr virus (EBV) biomarkers on the prognosis of HIV-related non-Hodgkin's lymphoma (NHL) has been poorly explored in the combined antiretroviral therapy (cART) era. Design: We evaluated EBV DNA load and EBV antibodies in HIV-NHL patients enrolled in the French ANRS-CO16 Lymphovir Cohort between 2008 and 2015. Methods: Whole blood and plasma EBV DNA load and serological profiles were analyzed in 76 HIV-infected patients at diagnosis of NHL and 6 months after the initiation of chemotherapy. Results: Prechemotherapy whole blood (WB) and plasma EBV DNA loads were positive for 80 and 45% of HIV-NHL patients, respectively. Pretreatment WB EBV DNA positivity was associated with a positive plasma HIV-1 RNA load (relative risk (RR), 4.42 [1.33; 14.72]) and plasma EBV DNA positivity with EBV in situ detection (RR 10.62 [2.38; 47.49]). Following chemotherapy, the proportions of patients with positive WB or plasma EBV DNA declined from 81 to 23% ( P  < 0.0001) and from 43 to 8% ( P  < 0.0001), respectively. Estimated 2-year progression-free survival did not differ according to prechemotherapy WB positivity (82% versus 67%, P  = 0.15) or plasma EBV DNA positivity (76% versus 81%, P   =  0.52). Conclusions: The plasma EBV DNA load correlates with in situ EBV detection. The WB EBV DNA load correlates with HIV load. WB and plasma EBV DNA loads at NHL diagnosis do not constitute prognostic markers for HIV-NHL patients in the modern cART era. Abstract : Supplemental Digital Content is available in the text